Application of K-impregnated staghorn coral as catalyst in the transesterification of waste cooking oil - Nabilah Atiqah Zul,; Shangeetha Ganesan,; M. Hazwan Hussin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This work focuses on the catalytic potential of K-impregnated staghorn coral as a catalyst in methyl esters production via methanolysis of waste cooking oil (WCO). The prepared catalyst was analyzed by Hammett indicators, XRF, Brunauer-Emmett-Teller (BET)-N2 adsorption method, ATR-FTIR, TGA, XRD and SEM to determine its physicochemical properties. ATR-FTIR and XRD results confirmed the formation of K2O species upon KOH impregnation, thus, resulting in good catalytic activity. Reaction parameters such as methanol to oil ratio, reaction time and amount of catalyst were evaluated to find out the best conditions for the transesterification process. About 89.51 ± 4.78 % of biodiesel contents were obtained under the optimum conditions.